ANALISIS TINJAUAN HUKUM ISLAM DAN HUKUM PERDATA TERHADAP PEMBUNUHAN SEBAGAI PENGHALANG KEWARISAN - Qoidul Khoir (Al Fuadiy Jurnal Hukum Keluarga Islam, 2022)
This discussion examines the analysis of Islamic Law and Civil Law reviews of murder as a barrier to inheritance recipients. The purpose of this paper is to provide an overview and explanation to the reader regarding the views of islamic figures/clerics' as well as the civil code regarding murders committed by a person as a barrier to the recipient of the inheritance. This research uses library research which is descriptive analysis based on text studies in the form of opinions of Islamic figures in the book of fiqh and civil law. The results showed that: The scholars of the Shafi'iyah school stated that all types of killings are an absolute barrier to inheritance. In the Compilation of Islamic Law it is also stated that the person who commits the act of murder is hindered in the acquisition of inheritance, as explained in article 173 paragraph 1. Meanwhile, in the civil code, it is also explained that murder can prevent the heirs from obtaining inheritance, as explained in article 838 paragraph 1. So it is very clear both according to islamic law and civil law that any form of murder committed by the heir against his heir will cause hindrance in obtaining the estate.